Nutritional and Sensory Properties of high Energy/Nutrient Dense Composite Flour Porridges from Germinated Maize and Roasted Beans for Child-Weaning In Developing Countries: A Case for Uganda - Kikafunda, Joyce K.; Abenakyo, Loy; Lukwago, Fred B. (Ecology of food and nutrition, 2006)
The study aimed at increasing the energy and nutrient density of traditional weaning porridges from germinated maize and decorticated bean flours. Proximate analysis showed that the porridge from the composite flour had a higher protein and energy density than typical weaning porridges made from maize alone. For a breastfed infant, the blend could meet 75% of the remaining required energy, compared to 52% provided by the porridge from maize alone. Untrained sensory evaluation panelists scored the porridge from the blend as acceptable. This blend therefore has great potential as a weaning food in resource-poor and technologically under-developed countries.
Keywords: weaning/complementary foods; developing countries; maize, germination